2023
DOI: 10.1111/clr.14210
|View full text |Cite
|
Sign up to set email alerts
|

Critical‐size defects reconstruction with four different bone grafts associated with e‐PTFE membrane: A histomorphometric experimental in vivo study

Gustavo Vicentis Oliveira Fernandes,
Filipe Castro,
Rafael Martins Pereira
et al.

Abstract: ObjectivesThe goal of this study was to assess the newly formed bone and the remnant biomaterial by comparing four different bone grafts used to treat critical‐size defects, associated or not with the non‐resorbable membrane.Materials and MethodsTwo calvaria critical‐size bone defects were created in 50 male Wistar rats. They were divided into blood (G1), autogenous (G2), bioglass (G3), hydroxyapatite (G4), and xenograft (G5) groups, associated or not with e‐PTFE. The experimental periods were 15 and 45 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…The sample size calculation was performed using ClinCalc.com, an online statistical calculator, to compare the results between two averages of a selected variable [26] in the same period (45 days). Previous results for newly formed bone area showed that group 1 (autogenous group) had 33.19% ± 10.7% of the percentual area, whereas group 2 (biomaterial, Bio-Oss ® ) had 11.90% ± 4.3%.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…The sample size calculation was performed using ClinCalc.com, an online statistical calculator, to compare the results between two averages of a selected variable [26] in the same period (45 days). Previous results for newly formed bone area showed that group 1 (autogenous group) had 33.19% ± 10.7% of the percentual area, whereas group 2 (biomaterial, Bio-Oss ® ) had 11.90% ± 4.3%.…”
Section: Sample Size Calculationmentioning
confidence: 99%